Evaluation of different setting configurations with a new developed telemedical interface of a parallel kinematic robotic system – An experimental development study. Issue 3 (9th February 2022) - Axt, Steffen; Dörflinger, Andreas; Johannink, Jonas; Kirschniak, Andreas; Rolinger, Jens; Wilhelm, Peter
Abstract: Background: For development of a minimally invasive intracorporal micromanipulator, a master‐slave telemanipulation system was required. Methods: Different input positions for a tablet‐based input device with a heads‐up centred screen were evaluated. Personal preference was assessed using a questionnaire. Then, the most ergonomic and intuitive position was compared to a surgical reference position based on laparoscopic sigmoid resection. Results: After comparing a 45°, 75° (pitch) and 60°/20° (pitch/yaw) to a 60° reference position no significant differences in processing time and number of failures could be demonstrated. Study participants indicated the 60°/20° position as the most comfortable in the questionnaire. This was therefore compared with the laparoscopic reference position, both sitting and standing. Here, the laparoscopic sitting position was perceived to be the most ergonomic. Conclusions: The developed input device offers a maximum of flexibility and individualisation to reach ergonomic and intuitive conditions. General recommendations regarding an optimal setting cannot be given, based on our results.